Estimating the time of infection for African swine fever in pig farms in Korea - Yoon, Hachung; Son, Youngmin; Kim, Kyung-Sook; Lee, Ilseob; Kim, Yeon-Hee; Lee, Eunesub (Frontiers in Veterinary Science, 2023)
African swine fever (ASF) outbreaks in pig farms significantly damage the entire pork industry. For an effective response, understanding the transmission dynamics of the ASF is important. Notably, it is important to know when the infection started on the outbreak farm. This study aimed at establishing a procedure for estimating the time of infection on pig farms affected by the ASF outbreak in Korea. The protocol for sampling to detect ASF virus infection, the estimation of the time interval between infection and detection based on simulation, and the estimation of the infection stage for the parameters of the simulation model were described. After infection, fattening sheds (9.8 days in median) had the longest detection time compared with pregnant (8.6 days) or farrowing sheds (8.0 days). The intervals were 8.8 days for farrow-to-finisher farms, 7.0 days for farrow-to-weaning farms, and 9.5 days for fattening farms. The findings of this study provide valuable insights into ASF outbreaks in pig farms thus, improving the disease control ability.